Influence of Plasma Fibronectin on the Response to Infusion of Thrombin and Adenosine Diphosphate - Kaplan, J E; Snedeker, P W; Baum, S H; Moon, D G; Minnear, F L (Thrombosis and Haemostasis, 1983)
An important physiological anti-thrombotic function has been suggested for plasma fibronectin and the reticuloendothelial system. The current study evaluated the effects of specific immunological fibronectin depletion and fibronectin supplementation upon resistance to infusion of thrombin and ADP in terms of mortality, mean arterial blood pressure and circulating levels of platelets, fibrinogen and fibrin degradation products. Mortality data indicated that rats with reduced fibronectin levels had reduced resistance to thrombin or adenosine diphosphate infusion. The increased lethality was characterized by reduced circulating levels of fibrinogen and platelets while fibrin degradation product levels rose. The infusion of ADP or thrombin in fibronectin supplemented rats failed to elicit higher mortality or reduce fibrinogen or platelet levels further. These data are consistent with the hypothesis that resistance to excessive coagulation and/or platelet aggregation is correlated to circulating plasma fibronectin levels. It is suggested that by direct effects and/ or acting as an opsonin for RES phagocytosis, plasma fibronectin acts as an important anti-thrombotic mechanism.
Keywords: Plasma fibronectin; Thrombosis; Reticuloendothelial system Adenosine diphosphate; Thrombin; Platelets; Fibrinogen